Acetate and auto‐inducing peptide are independent triggers of quorum sensing in Lactobacillus plantarum. Issue 1 (17th March 2021) - Meng, Fanqiang; Lu, Fengxia; Du, Hechao; Nie, Ting; Zhu, Xiaoyu; Connerton, Ian F.; Zhao, Haizhen; Bie, Xiaomei; Zhang, Chong; Lu, Zhaoxin; Lu, Yingjian
Abstract: The synthesis of plantaricin in Lactobacillus plantarum is regulated by quorum sensing. However, the nature of the extra‐cytoplasmic (EC) sensing domain of the histidine kinase (PlnB1) and the ability to recognize the auto‐inducing peptide PlnA1 is not known. We demonstrate the key motif Ile‐Ser‐Met‐Leu of auto‐inducing peptide PlnA1 binds to the hydrophobic region Phe‐Ala‐Ser‐Gln‐Phe of EC loop 2 of PlnB1 via hydrophobic interactions and hydrogen bonding. Moreover, we identify a new inducer, acetate, that regulates the synthesis of plantaricin by binding to a positively charged region (Arg‐Arg‐Tyr‐Ser‐His‐Lys) in loop 4 of PlnB1 via electrostatic interaction. The side chain of Phe143 on loop 4 determined the specificity and affinity of PlnB1 to recognize acetate. PlnA1 activates quorum sensing in log phase growth and acetate in stationary phase to maintain the synthesis of plantaricin under conditions of reduced growth. Acetate activation of PlnB was also evident in four types of PlnB present in different Lb . plantarum strains. Finally, we proposed a model to explain the developmental regulation of plantaricin synthesis by PlnA and acetate. These results have potential applications in improving food fermentation and bacteriocin production. Abstract : Auto‐inducing peptide PlnA1 and acetate bound to loop2 and loop4 of PlnB1, respectively, which activate the histidine kinase PlnB1.PlnA1 activates PlnB1 in the logarithmic phase and acetate in the stationary phase to regulate the synthesis of plantaricin in Lactobacillus plantarum .